2014
DOI: 10.1111/cei.12355
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide attenuates autoimmune arthritis severity in SKG mice via regulation of B cell and antibody production

Abstract: SummaryOxidative stress is involved in the pathophysiology of rheumatoid arthritis (RA). We investigated the therapeutic potential of rebamipide, a gastroprotective agent with a property of reactive oxygen species scavenger, on the development of inflammatory polyarthritis and the pathophysiological mechanisms by which rebamipide might confer anti-arthritic effects in SKG mice, an animal model of RA. Intraperitoneal (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
11
0
2
Order By: Relevance
“…TFH cells promote an immune response, while Breg cells inhibit an immune response. Rebampide treatment reduced the number of TFH cells, but increased the number of Breg cells, similar to our results. However, one study reported that TFH cells promoted IL‐10 production during the differentiation of Breg cells in systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 91%
“…TFH cells promote an immune response, while Breg cells inhibit an immune response. Rebampide treatment reduced the number of TFH cells, but increased the number of Breg cells, similar to our results. However, one study reported that TFH cells promoted IL‐10 production during the differentiation of Breg cells in systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a recent study showed that adjunct rebamipide therapy is also effective for preventing the occurrence of peptic ulcers in arthritic patients that are taking a COX-2-selective inhibitor [ 39 ]. It has been demonstrated that oral administration of rebamipide can reduce the clinical and histologic scores in animal models of rheumatoid arthritis, including collagen-induced arthritis and SKG mice [ 40 , 41 ]. There has been only one recent report regarding the inhibitory effects of rebamipide on pain production and cartilage degeneration in experimentally induced rat knee OA [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitor of Breg cells proliferation was reported as a suppressive factor of arthritis severity in RA murine model [35]. In this study, GCB cells expressing GL-7 are involved with the B cell immune response and Tfh cells revealing ICOS and PD-1 are involved in the germinal center responses.…”
Section: Q15mentioning
confidence: 67%